Effects of withdrawal speed on the structural, morphological, electrical, and optical properties of CuO thin films synthesized by dip-coating for CO2 gas sensing - A. M. M. Musa (AIP Publishing LLC, 2021)
Copper oxide (CuO) thin films have been deposited on glass substrates by a facile sol–gel dip-coating technique with varying withdrawal speeds from 0.73 to 4.17 mm/s. The variation in the film thickness manifested by dip-coating withdrawal speeds was investigated in detail to investigate its effect on the structural, morphological, opto-electrical, and wettability properties of CuO thin films for carbon dioxide (CO2) gas-sensing applications. The crystallinity, as well as phase purity of dip-coated CuO, was confirmed by both x-ray diffraction (XRD) and Raman spectral analyses. The surface morphology of the films characterized by scanning electron microscopy revealed that pore density decreases with increasing withdrawal speeds and the grain size is found to increase with the increasing film thickness corroborating the XRD results. The optical bandgap of dip-coated CuO films was estimated in the range of 1.47–1.52 eV from the UV–vis–NIR transmission data, and it is found to decrease with the increase in Urbach tail states accompanied by the increase in the film thickness. The ratio of the electrical and optical conductivity of CuO films was found to decrease with increasing withdrawal speeds due to the variation in the carrier concentration. Among all the studied films, the sample deposited at a 0.73 mm/s withdrawal speed exhibited the highest crystallinity, porous morphology, highest pore density, opto-electrical conductivity, as well as water contact angle and, therefore, the maximum gas sensing response of CO2 vapor in the air recorded at room temperature.